2012
DOI: 10.1177/0333102412447701
|View full text |Cite
|
Sign up to set email alerts
|

Primary trigeminal afferents are the main source for stimulus-induced CGRP release into jugular vein blood and CSF

Abstract: We conclude that resting state CGRP levels can be maintained after trigeminal denervation of the meninges. However, for functional purposes primary trigeminal afferents are mandatory as they are the major source for stimulus-induced CGRP release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…, ). In fact, CGRP in the peripheral circulation, due to activation of the trigeminovascular system, is principally released from the TG (Hoffmann et al ., ). Primary cultured TG neurons have been shown to express functional CGRP receptors (Zhang et al .…”
Section: Cgrp and Receptor Localization In The Trigeminovascular Systmentioning
confidence: 97%
See 1 more Smart Citation
“…, ). In fact, CGRP in the peripheral circulation, due to activation of the trigeminovascular system, is principally released from the TG (Hoffmann et al ., ). Primary cultured TG neurons have been shown to express functional CGRP receptors (Zhang et al .…”
Section: Cgrp and Receptor Localization In The Trigeminovascular Systmentioning
confidence: 97%
“…Stimulation of the TG by capsaicin, KCl or electrical impulse, results in the release of CGRP (Goadsby et al, 1988;Capuano et al, 2007). In fact, CGRP in the peripheral circulation, due to activation of the trigeminovascular system, is principally released from the TG (Hoffmann et al, 2012). Primary cultured TG neurons have been shown to express functional CGRP receptors (Zhang et al, 2007).…”
Section: Cgrp and Receptor Localization In The Trigeminovascular Systmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis of migraine biomarkers has shown that CGRP in CSF and blood was elevated in chronic migraine patients (glutamate and NGF were also increased), and levels of the endogenous opiate β‐endorphin decreased . Preclinically, it has been shown that cortical spreading depolarization/depression (CSD) may trigger the release of neuropeptides such as CGRP into the jugular vein and CSF from the primary trigeminal afferent fibers, where it could promote sensitization of the trigeminal system. In contrast, there are findings that suggest that acute activation of CGRP receptors may not play a key role in mediating CSD‐evoked headache, but CGRP‐mediated activation of meningeal afferents evoked by cortical efflux of potassium ion could promote headache.…”
Section: Questions To Ponder?mentioning
confidence: 99%
“…Trigeminal CGRP, through its roles in vasodilation, neurogenic inflammation, and peripheral sensitization, is likely to contribute to the most relevant peripheral actions in migraine . The main source of CGRP in migraine is primary trigeminal afferents, as plasma‐derived CGRP is unlikely to reach the ventroposterior medial thalamic nucleus because of poor penetration of the BBB . In the periphery, afferent endings of sensory neurons innervate blood vessels in almost every organ system, but the implications of CGRP release here in relation to migraine are unclear …”
Section: Expression and Functional Role Of Cgrp And Cgrp Receptors Inmentioning
confidence: 99%